(untitled) (Educational Dimension, 2021)
This article reveals the importance of multilingual knowledge in modern society and the need to introduce multilingual education. This article deals with the complexity of the process of development of polylingual personality, the influence of psychological factors on multilingual, the interconnection between linguistics and psychology. The components of the linguistic aspect of polylingualism and the essence of the concept of “psycholinguistics” are revealed. The article describes how language, speech, and comprehension correlate and interact with psychological processes. The results of theoretical generalizations of the subject and the importance of psycholinguistics are presented. The components of psycholinguistics and their significance are outlined. The stages of formation of psycholinguistics as science are investigated. The article substantiates the importance of developing a polylingual personality taking into account human psychological characteristics. Thanks to scientific conversation, it is shown that the understanding, processing and production of one and two languages in the human brain are significantly different from the same process in the brain of a multilingual man. These aspects are considered in view of the needs of multilingual education and to detect a number of psycholinguistic factors that are significant for the methodology of teaching several foreign languages.